Soluble ST2 as a Potential Biomarker in Pericardial Fluid of Coronary Artery Patients - Dikme,Reşat (2021)
Abstract Introduction: The growth Stimulation expressed gene 2 (ST2) (or interleukin 1 receptor-like 1, also known as IL1RL1) is considered a biomarker of poor prognosis in cardiovascular diseases. The aims of this study are to investigate ST2 in the pericardial fluid (PF) of coronary artery disease patients and to contribute to the understanding of the pathophysiology of coronary artery disease. Methods: 40 patients (blood plasma and PF) who underwent coronary artery bypass surgery and 40 controls (blood plasma only) were included in this study. Soluble ST2 (sST2) level was determined by enzyme-linked ımmunosorbent assay method in plasma and PF, and sST2 gene expression was determined by quantitative real-time polymerase chain reaction (QRT-PCR) method. Results: The sST2 level was found to be 44.89 ng/ml and 390.357 ng/ml in the control and patient groups’ plasma, and 223.992 ng/ml in the PF of the patient group. An increase in sST2 level was detected in the patient group compared to the control group (P<0.001). The sST2 expression in plasma was higher in the patient group than in the control group. Additionally, sST2 was more expressed in the plasma of the patient group than PF (P<0.001). Conclusion: The fact that sST2 was detected for the first time in a high level in PF showed that this biomarker was closely related with the heart and strengthened its potential to be used as a biomarker. Therefore, sST2 can contribute to the understanding of the pathophysiology of coronary artery disease.